1993
DOI: 10.1159/000177750
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutrients on Plasma Corticosteroid Concentration in Cold-Stressed Rats

Abstract: Little is known about the mechanisms as to how nutrients affect plasma corticosteroids in cold-stressed and starved animals. Therefore, cold-stressed rats (maintained at 7 °C) were fasted (control) or fed a balanced diet (casein 20wt%, fat 5 wt%, starch 70 wt% and vitamin-mineral premix 5 wt%) or the following dietary nutrients for 72 h: casein, lard, starch, glycerol, stearic acid, leucine or glutamic acid. The animals were then killed and plasma corticosteroid concentrations (PCC) were determined. PCC were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…To study the relationships among the nutrients, hormones and digestive enzymes in an "in vivo" model, we used a CEF (cold exposed fasted; negative control) and a CEBDF (cold exposed balanced diet fed; positive control) animal model based on our earlier study [1]. We hypothesized that in this cold exposed metabolic model the rats on the positive CEBDF ad libitum would be in zero energy balance while the negative CEF control animals were in maximum negative energy balance.…”
Section: Cold Exposed Fasted (Cef) and Cold Exposed Balanced Diet Fedmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the relationships among the nutrients, hormones and digestive enzymes in an "in vivo" model, we used a CEF (cold exposed fasted; negative control) and a CEBDF (cold exposed balanced diet fed; positive control) animal model based on our earlier study [1]. We hypothesized that in this cold exposed metabolic model the rats on the positive CEBDF ad libitum would be in zero energy balance while the negative CEF control animals were in maximum negative energy balance.…”
Section: Cold Exposed Fasted (Cef) and Cold Exposed Balanced Diet Fedmentioning
confidence: 99%
“…It has been shown that the timing of a meal [51] and the nutrient composition of the meal [52] influence plasma corticosteroid concentrations. The physiological mechanism(s) responsible for these alteration is/are not clear.…”
Section: Plasma Corticosteronementioning
confidence: 99%